2022
DOI: 10.1111/os.13560
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Effects of Resveratrol in Intervertebral Disc Degeneration: A Literature Review

Abstract: Intervertebral disc degeneration (IDD) is a high incidence disease of musculoskeletal system that often leads to stenosis, instability, pain and even deformity of the spinal segments. IDD is an important cause of discogenic lower back pain and often leads to large economic burden to families and society. Currently, the treatment of IDD is aimed at alleviating symptoms rather than blocking or reversing pathological progression of the damaged intervertebral disc. Resveratrol (RSV) is a polyphenol phytoalexin fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 107 publications
0
7
0
Order By: Relevance
“…It was also found that NRF1 induces autophagy and inhibits apoptotic responses by promoting Atg7 expression in compressed NP cells, delaying disc degeneration [73]. Phosphorylation of STAT3 accelerates NP apoptosis and intervertebral disc degeneration by degrading ECM [74].…”
Section: Discussionmentioning
confidence: 98%
“…It was also found that NRF1 induces autophagy and inhibits apoptotic responses by promoting Atg7 expression in compressed NP cells, delaying disc degeneration [73]. Phosphorylation of STAT3 accelerates NP apoptosis and intervertebral disc degeneration by degrading ECM [74].…”
Section: Discussionmentioning
confidence: 98%
“…The naturally occurring nonflavonoid polyphenol resveratrol (3,5,4′-trihydroxy-trans-stilbene) ( Figure 1 ) is a phytoalexin, produced as a stress response in plants for their protection against fungal infections [ 240 , 241 ]. It can be isolated from the roots of the herbaceous perennial plant Polygonum cuspidatum of the knotweed and buckwheat family Polygonaceae, but its presence has also been documented in trees (i.e., eucalyptus and spruce), in flowering plants (i.e., the lily species Veratrum grandiflorum and Veratrum formosanum ), in peanuts and groundnuts and in grapevines, grapes and red wine [ 242 , 243 , 244 ]. In nature, resveratrol can be found in cis- and trans-isomers, with the latter forms being the more biologically active due to the lower steric hindrance of their side chains [ 244 ].…”
Section: Plant-derived Compounds With a Reported Senotherapeutic Acti...mentioning
confidence: 99%
“…It can be isolated from the roots of the herbaceous perennial plant Polygonum cuspidatum of the knotweed and buckwheat family Polygonaceae, but its presence has also been documented in trees (i.e., eucalyptus and spruce), in flowering plants (i.e., the lily species Veratrum grandiflorum and Veratrum formosanum ), in peanuts and groundnuts and in grapevines, grapes and red wine [ 242 , 243 , 244 ]. In nature, resveratrol can be found in cis- and trans-isomers, with the latter forms being the more biologically active due to the lower steric hindrance of their side chains [ 244 ]. Resveratrol’s health benefits have long been recognized because numerous studies have shown its protective effects against various diseases, such as cancer, ischemic disease, neurodegenerative diseases, cardiovascular diseases, diabetes and OA [ 240 , 242 , 244 ], as well as its ability to increase lower organisms’ lifespan and to generally improve the health of mammals [ 245 ].…”
Section: Plant-derived Compounds With a Reported Senotherapeutic Acti...mentioning
confidence: 99%
See 1 more Smart Citation
“…Natural products extracted from medicinal plants have garnered growing attention because of their biological and clinical therapeutic effects with fewer side effects. [6][7][8] Panax ginseng C.A. Meyer is one of the most widely used herbal medicines in East Asia.…”
Section: Introductionmentioning
confidence: 99%